Self-healing of cyclic loading damage in asphalt mixtures - Salih, Siham Idan (2020)
One of the essential phenomena that impacts on the properties of asphalt mix is the self-healing. This phenomenon has been explored for about four decades. However, many researchers are trying to investigate artificial methods to accelerate it. The present study was primarily aimed to investigate the optimum moment in the life of asphalt, where self-healing is maximized. Three different self-healing techniques have been investigated, namely infra-red heating, induction heating, and encapsulated healing agents. Accomplishing this aim would enable self-healing to be incorporated into a maintenance plan of the pavement. This study commenced with a literature review concerning the asphalt self-healing phenomenon, in order to identify the current gaps that must be researched. There are no previous studies about the optimum moment to implement artificial self-healing. For this reason, further research in this thesis was arranged to assess the self -healing capability of hot asphalt mixtures in further detail. Three different asphalt mixtures were used such as; Porous asphalt (PA), Dense asphalt (DA), and Stone mastic asphalt (SMA). Three methods were utilized to generate self-healing: Infra-red heating, Induction heating and Capsules containing rejuvenators. In addition, many tests were carried out : (i) 3-point bending fatigue test to quantify self-healing, (ii) X-Ray Computed Tomography (CT Scans) to assess air void distribution before and after healing, and (iii) Additional testing related to self-healing for example; Thermal expansion, Stiffness module’s (ITSM), and Fourier Transformed Infrared Spectroscopy (FTIR). These test methods covered the three following aspects. The first aspect of research used infrared heating to simulate solar radiation. It explored the effect of air voids content and their interconnectivity on the capacity of asphalt mixtures to heal fatigue cracks when a thermal infrared treatment is applied. Results showed that contiguous air voids are required to optimise healing. In samples with a lower void content, the thermal expansion of bitumen and its flow through cracks can exceed the pore network’s capacity. Therefore, the internal pressure can increase enough to produce material damage instead of healing. Also, the fatigue life of dense asphalt mixes is still significantly longer than that of porous asphalt mixtures. On the contrary, asphalt mixtures with percolated air void content got higher fatigue life extensions than denser asphalt mixtures, to the point of tripling their lifetime. The second aspect researched used another self-healing method namely induction heating to evaluate self-healing ability. Electrically conductive particles in the form of steel wool fibres were added into porous asphalt (PA). In previous publications, it was found that this technique can significantly extend the fatigue life of the material but the optimum moment to apply the treatment had still unknown not been investigated in-depth by other researchers. In the present investigation, fatigue tests were carried out at different loading levels and the optimum time in the life of the material to apply the induction treatment was found to be at 35% of the failure life based on statistics and Computed Tomography scans. The results also show that Induction heating reduces the diameter of the air voids. As a consequence, this has lead to enhancement of the life of the pavement. The third aspect considered of a study of the self-healing of asphalt mixture enhanced by capsules. The self-healing properties of cracks were then examined under repeated loading in dense, porous, and Stone Mastic Asphalt (SMA) asphalt mixtures, which are the most commonly used asphalt types worldwide. The study determined the optimum time that is represented 35% of number of cycles N0.5 (probability of breaking) when the capsules should break to maximise the self-healing. It also gave an insight into the type of cracks that already heal and the breaking mode of the capsules due to repeated loading. Based on the results obtained for three aspects above, a good understanding of the self- healing of asphalt was achieved. This thesis concludes by discussing these important aspects of constructing of pavements with high durability provided by self-healing abilities. Self-healing asphalt is not only a dream; it works. In addition, porous and stone mastic asphalt healed more efficiently than dense asphalt. One of the essential phenomena that impacts on the properties of asphalt mix is the self-healing. This phenomenon has been explored for about four decades. However, many researchers are trying to investigate artificial methods to accelerate it. The present study was primarily aimed to investigate the optimum moment in the life of asphalt, where self-healing is maximized. Three different self-healing techniques have been investigated, namely infra-red heating, induction heating, and encapsulated healing agents. Accomplishing this aim would enable self-healing to be incorporated into a maintenance plan of the pavement. This study commenced with a literature review concerning the asphalt self- healing phenomenon, in order to identify the current gaps that must be researched. There are no previous studies about the optimum moment to implement artificial self-healing. For this reason, further research in this thesis was arranged to assess the self-healing capability of hot asphalt mixtures in further detail. Three different asphalt mixtures were used such as; Porous asphalt (PA), Dense asphalt (DA), and Stone mastic asphalt (SMA). Three methods were utilized to generate self-healing: Infra-red heating, Induction heating and Capsules containing rejuvenators. In addition, many tests were carried out : (i) 3-point bending fatigue test to quantify self-healing, (ii) X-Ray Computed Tomography (CT Scans) to assess air void distribution before and after healing, and (iii) Additional testing related to self-healing for example; Thermal expansion, Stiffness module’s (ITSM), and Fourier Transformed Infrared Spectroscopy (FTIR). These test methods covered the three following aspects. The first aspect of research used infrared heating to simulate solar radiation. It explored the effect of air voids content and their interconnectivity on the capacity of asphalt mixtures to heal fatigue cracks when a thermal infrared treatment is applied. Results showed that contiguous air voids are required to optimise healing. In samples with a lower void content, the thermal expansion of bitumen and its flow through cracks can exceed the pore network’s capacity. Therefore, the internal pressure can increase enough to produce material damage instead of healing. Also, the fatigue life of dense asphalt mixes is still significantly longer than that of porous asphalt mixtures. On the contrary, asphalt mixtures with percolated air void content got higher fatigue life extensions than denser asphalt mixtures, to the point of tripling their lifetime. The second aspect researched used another self-healing method namely induction heating to evaluate self-healing ability. Electrically conductive particles in the form of steel wool fibres were added into porous asphalt (PA). In previous publications, it was found that this technique can significantly extend the fatigue life of the material but the optimum moment to apply the treatment had still unknown not been investigated in -depth by other researchers. In the present investigation, fatigue tests were carried out at different loading levels and the optimum time in the life of the material to apply the induction treatment was found to be at 35% of the failure life based on statistics and Computed Tomography scans. The results also show that Induction heating reduces the diameter of the air voids. As a consequence, this has lead to enhancement of the life of the pavement. The third aspect considered of a study of the self-healing of asphalt mixture enhanced by capsules. The self-healing properties of cracks were then examined under repeated loading in dense, porous, and Stone Mastic Asphalt (SMA) asphalt mixtures, which are the most commonly used asphalt types worldwide. The study determined the optimum time that is represented 35% of number of cycles N0.5 (probability of breaking) when the capsules should break to maximise the self-healing. It also gave an insight into the type of cracks that already heal and the breaking mode of the capsules due to repeated loading. Based on the results obtained for three aspects above, a good understanding of the self- healing of asphalt was achieved. This thesis concludes by discussing these important aspects of constructing of pavements with high durability provided by self- healing abilities. Self-healing asphalt is not only a dream; it works. In addition, porous and stone mastic asphalt healed more efficiently than dense asphalt.